Synchronous Interactions Foster Empathy. (July 2019) - Levy, Jonathan; Feldman, Ruth
Despite growing interest in the neuroscience of empathy, very little is known about the developmental processes that foster the neural maturation of an empathic response. Here, we suggest that the synchronous interaction shapes and fosters the ability to empathize with others. We argue that this intriguing relationship between synchrony and empathy expands beyond the mother-child relationship to social relationships in general. It will be important to further explore this relationship in more social settings and to probe the biological mechanisms, which may underlie it. Advancing research on the relationship between these two social processes may support the work of practitioners, psychologists, and educators in moderating the devastating outcomes of mental disorders and promoting social maturity and growth.